Determination of energetic properties of wood and charcoal produced from Eucalyptus benthamii Determinação das propriedades energéticas da madeira e do carvão vegetal produzido a partir de: Eucalyptus benthamii - Nones D.L.* (2015)
This research aimed to characterize the energetic properties of wood and charcoal obtained from Eucalyptus benthamii for two different ages, 5 and 13 years. For each timber age, we prepared 48 specimens, approximately 2 x 2 x 2 cm, used to determine specific gravity, calorific value, immediate analysis and carbonization. After carbonization, we evaluated the energetic properties of the charcoal in relation to density, gravimetric and volumetric yield, calorific value and immediate chemical analysis. As the wood as charcoal were influenced by age. The 13 years old timber revealed higher specific gravity and higher calorific value. However, the differences in the physical and energetic properties of the wood of the two ages do not justify maintaining the forest until the age of 13, as its end use is generation of energy as coal. The charcoal produced from 13 years old trees had the highest yield, while the charcoal from 5 years old trees had better quality to energy usage.